THE PRINCIPLE OF POWERING SEVERAL EMITTERS WITH ONE POWER LINE - Ilnytskyi, Ludvig; Mikhalchuk, Inna; Shcherbyna, Olga (Science-based technologies, 2024)
In some cases, when using mobile radio centers to provide communications, information transmission, and operational management of specific activity types, difficulties arise with antenna systems deployment. This is especially critical when the radio center has to be frequently moved from one location to another and if the radio center serves several zones on different frequency channels. With a significant radius of the service area, the difficulties increase, since the antenna devices must be raised to the certain height above the earth's surface. Using the power supply of several antennas from one feeder, it is possible to reduce the deployment time of antenna devices and the number of masts, which will allow more rational use of the allocated territory for the radio center, reduce the cost of antenna structures and simplify the conditions for relocating the radio center, facilitate the choice of the location for installing masts, etc. Considering the importance of feeding several antennas using single radio frequency line and the significance of the consequences that arise when using the feeder built on single transmission line, this article identifies the problems and solutions associated with the operation of the multi-channel power supply device for radiation systems. According to the above comments, the feeder must have at least linear passive lossless eight-port network (three inputs and one output) for combining several independent flows of electromagnetic energy generated by transmitters, the radio frequency transmission line for transporting electromagnetic energy, and second eight-port network (one input and three outputs) for isolating energy flows and feeding them to the inputs of antenna devices. Since the main identification feature of each energy flow is the oscillation frequency, it is advisable to build such eight-terminal networks based on bandpass filters. In order for the feeder device to function in a stable mode, this work defines the main parameters of the filters, allowing to design and manufacture the filters themselves and analytically justify the choice of filter connection points to the transmission line.